The Influence of Entrepreneurship Subject on Students’ Interest in Entrepreneurship by Hidden Curriculum as Intervening Variable (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to know the influence of entrepreneurship subject on students’ interest in entrepreneurship at Institute of Mathaliul Falah (IPMAFA) in Pati by hidden curriculum as intervening variable. The research used WarpsPls analysis to test model directly and directly. Samples of the study were 30 Islamic banking students who got entrepreneurship subject and Islamic community development who did not get the entrepreneurship subject. Findings show that the entrepreneurship subject influences students’ interest in entrepreneurship and the second model test results showed that hidden curriculum is not able to become the intervening variable for students’ interest in entrepreneurship subject on students’ interest in entrepreneurship.